The Meaning Of Qawm In The Qur’an: A Semantic Analysis Based On Thoshihiko Izutsu’s Approach - Erifca Annisa; Masruchin Masruchin; Beko Hendro (Insitut Muslim Cendekia, 2025)
Qawm is one of the terms used in the Qur’an to refer to a group of people. Using a qualitative study with an analytical descriptive approach based on library research, this study explored the meaning of the word qawm in the Qur’an through the semantic approach of Toshihiko Izutsu. The aimed of this study was to uncover the true meaning of qawm and formulate a final conclusion regarding the weltanschauung or worldview associated with the term. The semantic analysis based on Izutsu’s method involves several steps: identifying the key term, determining its basic and relational meanings, revealing its historical development, and finally describing the weltanschauung of qawm in the Qur’anic context. The findings showed that in the Qur’an, qawm does not merely signify a group based on ethnicity or culture, but rather a community evaluated through their attitude toward divine teachings. The term encompasses both men and women who live together as a group. The Qur’an classifies qawm into two categories: positive characters—those who believe in and obey Allah; and negative characters —those who reject His teachings and ultimately face destruction. This view indicated that the Qur’an does not judge people based on their origins, but on their faith and moral character. Thus, the concept of qawm reflects the Qur’anic worldview that highlights the importance of spiritual and ethical values in shaping both individual and collective identity.